Manajemen Supervisi Klinis Untuk Meningkatkan Profesionalisme Guru Di Sekolah Menengah Atas Kolese De Britto Yogyakarta - Yohanes Umbu Lede (Jurnal Edukasi Sumba (JES), 2020)
The research aimed to know the clinical supervission management to improve teacher’s professionalism in Senior High School of Kolese De Britto Yogyakarta.This research was conducted in Senior High School of Kolese De Britto Yogyakarta. The collecting data method were interview, observation and documentation. The informan in this research were principal, teachers and supervisor. The data validity were done by triangulation techniques. The data were analyzed by interactive analysis model.Results of the research showed that: (1) Clinical supervision management to improve teachers professionalism in Senior High School of Kolese De Britto Yogyakarta was successful. Supervission management in grew continuously and systematically. Supervisors understand and know about clinical supervision properly, help and guidance teachers with aims for learning emendation. (2) Professional competence of teachers which felt needs to understood and well known at Senior High School Kolese De Britto are competences of professional teachers based on vision and mission in school. The competences mentioned is suitable with school vision and mission based on leadership competence. (3) Senior High School Kolese De Britto as educational institutions, support Ignatian spirituality. The term of this spiritual is risen from the knowledge about contexts, action, reflection, and evaluation. The learning quality is not only just about transfer of knowledge, but also about values. (4) Supporting factors in the management of clinical supervision include a culture and school management, initiative and transparency of a teacher, and human resources that support, institution staffs and foundation give PKG and FDG socialization, and evaluation activities. (5) Constraints factors in implementation of clinical supervision management are: erroneous paradigms about clinical supervision (supervision is still looked and understood as an assessment for a teacher performance), time for teaching is demanding schedule, there are unnatural situation and action in the class, there are some teachers don’t have openhanded when under strict, there are psychology constraint, and achievable of using technology based on IT.